25 Years of Complex Intervention Trials: Reflections on Lived and Scientific Experiences. (July 2018) - Komro, Kelli A.
For the past 25 years, I have led multiple group-randomized trials, each focused on a specific underserved population of youth and each one evaluated health effects of complex interventions designed to prevent high-risk behaviors. I share my reflections on issues of intervention and research design, as well as how research results fostered my evolution toward addressing fundamental social determinants of health and well-being. Reflections related to intervention design emphasize the importance of careful consideration of theory of causes and theory of change, theoretical comprehensiveness versus fundamental determinants of population health, how high to reach, and health in all policies. Flowing from these intervention design issues are reflections on implications for research design, including the importance of matching the unit of intervention to the unit of assignment, the emerging field of public health law research, and consideration of design options and design elements beyond and in combination with random assignment.